Shear Behavior and Anisotropy Characteristics of the Fracture Morphology of Sandstone with Different Water Contents. (12th February 2020) - Du, Changang; Sun, Lulu; Qin, Botao; Xu, Jiang; Liu, Yixin
Abstract : Hydromechanical coupling in rock masses is an important issue for many rock mechanics and hydrogeology applications. The change of a water-bearing state will induce the fracture of the intact rocks and further accelerate the shear slip instability of the sheared surface. To investigate the weakening effect of water content on the mechanical properties of a rock mass, laboratory direct shear tests combined with three-dimensional analysis of sheared surfaces were carried out on sandstone samples with different water contents. The variogram parameters, sill and range, were applied to quantify the morphology of shear fracture surfaces, to reflect the shear failure process of the intact rock, and to provide a basis for resliding instability of jointed rock. It was determined that the sill represents the height of the fluctuation body in the fracture surface and the range represents the single fluctuation body and may reflect the frequency of fluctuations. The test results revealed that the increase in water content had a clear weakening effect on the shear strength and deformation behavior of rock, especially under saturated conditions. Moreover, the distribution of water in the samples directly affected the crack initiation and propagation and characteristics of the fracture morphology.